The risk assessment of sleep duration on geriatric sarcopenia and its regulatory role in the effect of BMI index on geriatric sarcopenia based on the CHARLS database - Yan Chen; Xue-Ke Shi; Nan-Nan Liu; Zhihai Feng (PLoS ONE, 2026)
Background The effect of sleep duration on geriatric sarcopenia remains unclear, and evidence of the combined impact of it and BMI on geriatric sarcopenia is scarce. Aims To conduct the risk assessment of sleep duration on geriatric sarcopenia and explore its moderating role in the effect of BMI on geriatric sarcopenia based on the CHARLS database. Methods Data were extracted from the China Health and Retirement Longitudinal Study (CHARLS) 2011, 2013, and 2015 waves respectively. Logistic regression and Cox regression analyses were conducted to assess the risk of sleep duration for geriatric sarcopenia, and the regulatory effect of sleep duration on the association between BMI and sarcopenia. Subgroup analysis was conducted to enhance the stability of the results. Results The four abnormal types of sleep duration were significantly associated with sarcopenia. A significant association between obesity and decreased risk of sarcopenia was observed in sufficient sleep and sleep deprivation groups after the full adjustment of covariates (Adjusted HR = 0.25, 95%CI: 0.10–0.64, P < 0.001; Adjusted HR = 0.13, 95%CI: 0.03–0.53, P = 0.004; Adjusted HR = 0.26, 95%CI: 0.10–0.66, P = 0.005), and relationships of underweight and overweight with sarcopenia were observed in sufficient sleep, sleep deprivation, and mild oversleeping groups. In the group of oversleeping, the associations were not significant. Conclusion Abnormal sleep durations including sleep deprivation and oversleeping are linked to a heightened risk of sarcopenia among older adults. Underweight is associated with the increased sarcopenia risk, and overweight is correlated with the decreased risk of sarcopenia, especially in females with abnormal sleep duration except for severe oversleeping, and obesity is associated with the decreased risk of sarcopenia, especially in adults aged over 65 with sleep deprivation.